Attenuated total reflection‐cascading nanostructure‐enhanced Raman spectroscopy on flat surfaces: A nano‐optical design. (15th October 2020) - You, En‐Ming; Wang, Hai‐Long; Zheng, Jun‐Rong; Meng, Zhao‐Dong; Zhang, Mao‐Xin; Ding, Song‐Yuan; Tian, Zhong‐Qun
Abstract: The surface‐enhanced Raman scattering (SERS) effect was discovered by Richard Van Duyne et al. in 1977. He and coworkers also first utilized an innovative strategy that used SERS to record spectra on such SERS‐inactive substrate surfaces as n‐gallium arsenide (100) surfaces, which were modified by silver nano‐islands. This nanostructure‐enhanced Raman spectroscopy on flat surfaces (NERSoFS) enabled such SERS applications to be expanded to a variety of materials by virtue of SERS‐active nanostructures such as Au or Ag nanoparticles and shell‐isolated nanoparticles. However, most of such systems, although yielding Raman spectra, produce rather low enhancements, especially when used to record spectra on flat surfaces of SERS‐inactive materials. In this work, along with the direction of Van Duyne's borrowing‐SERS strategy and on the basis of the strategy of cascading optical coupling, we consider a theoretically designed optical configuration, based on an attenuated total reflection‐cascading nanostructure to produce enhanced Raman spectroscopy (ATRc‐NERS) on flat surfaces. This system can effectively harvest the incident light, thereby boosting the local optical field of the incident light and also moderately increasing the radiation field of the Raman‐scattered signals. In this way, one can gain 1–2 additional orders of magnitude in Raman enhancement over present NERSoFS systems both on metallic and nonmetallic flat surfaces, which are otherwise SERS‐inactive. This ATRc‐NERS strategy can potentially be used to develop ultrasensitive and versatile tools for surface science, material science, catalysis, electrochemistry, and micro‐electronics and micro‐LED industries. Abstract : A hierarchical structure is designed and proposed for ATRc‐SHINERS to further improve the surface sensitivity of the SHINERS configuration by up to two orders of magnitude by employing an ATR prism coupled with the SHINs‐substrate systems. The additional enhancement for flat nonmetallic or metallic substrates is essentially important for widely practical applications.